Global outcomes and prognosis for relapsed/refractory mature T-cell and NK-cell lymphomas: results from the PETAL consortium - Jessy Xinyi Han; Min Jung Koh; Leora Boussi; Mark Sorial; Sean M. McCabe; Luke Peng; Shambhavi Singh; Ijeoma Julie Eche-Ugwu; Judith Gabler; Maria J. Fernandez Turizo; Caroline T. MacVicar; Aditya Garg; et al. (Blood Advances)
Abstract: Variances in global access to drugs and treatment practices make it challenging to understand the benefit of contemporary therapies in patients with relapsed and refractory (R/R) mature T-cell and natural killer–cell lymphomas (MTCL and MNKCL). We conducted an international retrospective cohort study of 925 patients with R/R MTCL and MNKCL. In peripheral T-cell lymphoma–not otherwise specified and anaplastic lymphoma kinase–negative anaplastic large cell lymphoma (ALK– ALCL), patients with relapsed lymphoma demonstrated a superior median overall survival (OS) relative to refractory from the time of second-line treatment. We identified several independent predictors of OS for R/R lymphoma including age >60 years, primary refractory disease, histological subtype other than angioimmunoblastic T-cell lymphoma (AITL), extranodal sites >1, Ki67 ≥40%, and absolute lymphocyte count less than the lower limit of normal. A multivariable model incorporating these formed the basis for a prognostic index for R/R TCL, in which patients are stratified into low-risk (0-1 risk factor), intermediate-risk (2-3 risk factors), or high-risk (≥4 risk factors) groups, which were associated with 3-year OS of 57.14%, 23.3%, and 7%, respectively. Patients received either a ''novel'' single agent (SA; 35%) or cytotoxic chemotherapy (CC; 60%) for their second-line treatment. Higher progression-free survival was observed with SA over CC for the entire cohort with a higher 3-year OS in AITL and ALK– ALCL. Among the SA, small-molecule inhibitors demonstrated OS advantage relative to CC in AITL. Our results highlight continued efficacy of novel drugs globally and the potential of a new prediction model in informing heterogeneous prognosis within the R/R population of MTCL and MNKCL.